2000
DOI: 10.1023/a:1008947201132
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study provides, at best, only weak evidence for the hypothesis that calcium and phosphorus are independently associated with prostate cancer risk, but suggests that there may be an interaction between these nutrients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(13 citation statements)
references
References 31 publications
1
10
0
2
Order By: Relevance
“…The discrepancy in results may be due to the fact that we classified advanced disease based on TNM stage and Gleason grade, whereas Mitrou et al’s definition was based solely on the former criterion. In our study, there was no association between red meat and prostate cancer risk, which is consistent with a prior ATBC publication based on only 184 cases 32 .…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy in results may be due to the fact that we classified advanced disease based on TNM stage and Gleason grade, whereas Mitrou et al’s definition was based solely on the former criterion. In our study, there was no association between red meat and prostate cancer risk, which is consistent with a prior ATBC publication based on only 184 cases 32 .…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of Pca cases was about 60.60 years and the mean follow-up period was 9.2 years. Four studies [ 29 , 30 , 33 , 37 ] measured fat intake with energy percentages and the remaining 10 measured grams [ 8 , 32 , 34 36 , 38 – 41 ]. All of the studies were conducted in America or European countries and America (America and Canada) contributed 84.71% of total cases.…”
Section: Resultsmentioning
confidence: 99%
“…66 These data may partly explain our results for vitamin D and calcium and NHL risk. However this mechanism has been investigated more extensively in studies of prostate cancer 67,68 with data showing a complex relationship among vitamin D receptors, calcium and vitamin D metabolite levels that is tissue specific. Interestingly, one NHL study to investigate vitamin D receptor (VDR) polymorphisms showed some evidence that sun exposure and vitamin D intake may increase risk of FL among carriers of a variant allele in VDR.…”
Section: Discussionmentioning
confidence: 99%